2017
DOI: 10.1002/jgh3.12003
|View full text |Cite
|
Sign up to set email alerts
|

Drug resistance in intestinal tuberculosis: A reason to worry?

Abstract: Background and AimEmergence of drug resistance in intestinal tuberculosis (ITB) makes the treatment of this condition challenging. While there is growing evidence of multiple and extensive drug resistance in pulmonary and glandular tuberculosis (TB), literature regarding susceptibility and resistance patterns in ITB is scarce. The aim of the current paper was to study the prevalence of drug resistance in patients with ITB.MethodsAmong patients presenting to a tertiary care hospital in Mumbai between 2008 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
0
4
1
Order By: Relevance
“…This phenomenon could be attributed to the abundant tissue obtained by peritoneoscopy. Gene Xpert also detected MDR TB in two patients (7.14%) in the current study which was less as compared to the other study published from Mumbai [22]. Notably, we could diagnose tuberculosis and rifampicin resistance within four hours, which otherwise could have taken four days to four weeks.…”
Section: Discussioncontrasting
confidence: 90%
“…This phenomenon could be attributed to the abundant tissue obtained by peritoneoscopy. Gene Xpert also detected MDR TB in two patients (7.14%) in the current study which was less as compared to the other study published from Mumbai [22]. Notably, we could diagnose tuberculosis and rifampicin resistance within four hours, which otherwise could have taken four days to four weeks.…”
Section: Discussioncontrasting
confidence: 90%
“…The prevalence of MDR-TB in GITB is not very well-studied because the culture sensitivity is low and testing for drug resistance is not routinely done. The few studies that examined this had a modest study sample size and reported a prevalence of single-drug and multi-drug resistance ranging from 4 to 25% and 3 to 25%, respectively[ 126 127 128 129 130 ] [ Table 4 ]. Confirmation of MDR-TB in GITB is important to ensure that the patient gets the most appropriate treatment regimens and to avoid unnecessary delay in the therapy.…”
Section: Treatmentmentioning
confidence: 99%
“…Several studies have reported drug resistance in GITB. In a culture-based study from Western India, of the 43 patients with culture positivity, 23% had resistance to at least one first-line drug, while 14% had MDR-TB [77]. In a recent study on 30 ileocecal biopsies with positive TB cultures, four each (13.3%) had isoniazid and MDR, while two each (6.7%) were pre-extremely drug resistant (XDR) and mono-fluoroquinolone resistant [78].…”
Section: Drug Resistancementioning
confidence: 99%